Right to education of children in detention institutions in Malaysia - Noor Aziah Mohd Awal,; Siti Hajar Jamal,; Mohd Al Adib Samuri,; Fariza Md Sham,; Mohd Ikhwan Ismail,; Nurul Izzah Zainol,; Mohd. Adli Baco, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Academic education for children in detention institutions is a component of rehabilitation programs designed to encourage and shape positive behaviour. The objective of this study is to identify how far children in detention are given access to education as their basic human right. This research began by distributing questionnaires to 479 respondents and in-depth interviews with 72 children in six zones: north, middle, south, east, Sabah, and Sarawak. The researchers also conducted interviews in two separate focus group discussions, where each group comprised 4 to 6 officers who are experts in handling children in detention. The quantitative data research findings showed that the overall mean value for detained children's level of access to the right to academic education in their respective detention institutions was medium (Mean: 3.64, SP: 0.68). Based on 16 items that measure the right to academic education, the mean for each item scored between 2.77 to 4.20, demonstrating that the respondents gave medium to high scores regarding the right to academic education for children in detention institutions in Malaysia. The findings of the interviews revealed three sub-themes from an educational aspect, which are: (i) challenges in teachers' services, (ii) limited access to an academic program, and (iii) lack of learning facilities. Hence, this study can serve as a guideline to the Government and international agencies to collaborate in a joint effort to increase the quality of education service to children in detention centres.